Funcionalização e caracterização do carbon black vulcan XC–72R para aplicações em biossensores baseados em inibição enzimática - Ibáñez Redín, Glenda Gisela (2016)
In this work, carbon black Vulcan XC-72R was functionalized using five different treatments, the oxidizing agents employed were: nitric acid, sulfuric acid and hydrogen peroxide. The physical characterization of functionalized samples was carried out using scanning electron microscopy (SEM) and Raman spectroscopy. The results suggested that the treatments did not significantly alter the morphology of the material in most cases and showed an increase in the number of defects attributed to the introduction of oxygenated functional groups. Glassy carbon electrodes (GCE) were modified with aqueous dispersions of materials in dihexadecyl hydrogen phosphate (DHP). For the electrochemical characterization of the electrodes were performed studies of cyclic voltammetry employing the probe potassium hexacyanoferrate (III). For all cases there was an increase in the electroactive area as a result of the functionalization. Subsequently, the response of the electrodes to different analytes (dopamine, catechol, paracetamol and hydroquinone) was evaluated, the electrode modified in a mixture of nitric and sulfuric acid 1:1 (CB–HNO3/H2SO41:1–DHP/GCE) showed the highest analytical signal for the different compounds tested. Calibration curves were constructed for the determination of dopamine using the GCE electrode, the electrode prepared with unmodified CB (CB–DHP/GCE) and the CB–HNO3/H2SO41:1–DHP/GCE electrode, the sensitivities of the analytical curves (angular coefficients of the analytical curves) were: 0.334, 3.65 and 6.54 A cm−2 L mol−1, respectively. These results show a significant increase in sensitivity as a result of the functionalization xvii of CB suggesting an advantage over the use of unmodified material for electroanalytical applications. Then, an analytical procedure for the determination of sodium benzoate (sodium salt of benzoic acid) based on enzyme inhibition was developed, where the tyrosinase enzyme was immobilized at the surface of the CB– HNO3/H2SO41:1–DHP/GCE electrode (biosensor). Studies of the inhibition mechanism and optimization of operating conditions were performed. The corresponding analytical curves had linear concentration ranges between 4.90 × 10−7 and 1.92 × 10−5 mol L−1 and a detection limit of 2.1 × 10−7 mol L−1.